2016
DOI: 10.1615/plasmamed.2016018933
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Analysis of Plant Seeds Irradiated by Active Oxygen Species in Oxygen Plasma

Abstract: Gene expressions in plant seeds irradiated by oxygen plasma were investigated using DNA microarray bioinformatics analysis to clarify the pathways responsible for growth enhancement of plants. Gene expressions involved in photosynthesis and energy production growth enhancement of plants is brought about by epigenetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…These changes by the plasma treatment in the short-term may be due to epigenetics such as regulating DNA cytosine methylation, which inactivates gene expression [74,184].…”
Section: Epigenetics and Geneticsmentioning
confidence: 99%
“…These changes by the plasma treatment in the short-term may be due to epigenetics such as regulating DNA cytosine methylation, which inactivates gene expression [74,184].…”
Section: Epigenetics and Geneticsmentioning
confidence: 99%
“…After NTP treatment of seeds, the expression of several genes changed. Hayashi et al [ 26 ] found the upregulation of genes involved in increasing energy production by photosynthesis by upregulating enzymes such as RuBisCO, increasing carbon fixation and production of the plant hormone auxin. Nakano et al [ 27 ] also noted changes in the synthesis of several proteins, but it appears that there were no mutagenic effects on seed embryos in genes associated with plant growth, as the growth increase was not inherited from the first plant generation.…”
Section: Nonthermal Plasma Effects On Seedsmentioning
confidence: 99%
“…It is important to know whether the effects have an impact on seeds and plants of future generations. Hayashi et al [ 26 ] reported that the growth of second-generation plants was similar to that of seeds not treated with NTP, indicating that no mutation of growth-related genes occurred during the NTP treatment of first-generation seeds. Gene expression analysis of Arabidopsis thaliana seeds, however, showed a different gene expression pattern in the second-generation compared to the first-generation seeds.…”
Section: Nonthermal Plasma Effects On Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, useful effects of plants such as enhancements of germination, growth and antioxidative activity have been investigated, which are induced by active particles in plasmas [1][2][3][4][5][6][7][8][9][10][11]. Enhancements of root and stem lengths and leaf area have been observed [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%